Municipal government in Great Britain - Spilman, Harold Addison (My University, 1903)
Introduction: Within the last few years events in some of our larger cities have caused no little agitation regarding municipal government and municipal reform. That public attention should be turned to such matters is eminently proper, and in fact, necessary. Good municipal government is essential to the continued good government of a nation. To-day over one-third of our people reside in cities of over eight thousand inhabitants and as the country increases in age the percentage will increase. Anything which so directly affects the welfare of one-third of our population should deeply concern, not only that one-third, of our population should deeply concern, not only that one-third, but the other two-thirds as well. Bryce says that there are “two tests of the practical efficiency of the government of a city: what does it provide for the people and what does it cost the people. Measured by these tests, it has become more and more evident in recent years that municipal administration in this country is a disgraceful failure. A failure because the people have paid tens, perhaps hundreds, of thousands of dollars for that which could have cost them thousands only, and have received therefore inefficient police service, defective paving, poor work of every kind. Disgraceful because of the boodling and corruption and viciousness which have caused such extravagance. It would seem that, although we have given the world what is probably the most perfect form of national government, yet, in this matter of municipal administration we still have much to learn; and in this event it is but natural that we should turn to the older countries of Europe and see in what manner that have solved this problem. Naturally, in any such study, one looks first to the country from whose institutions are derived, in part, our own principles of government. And there we find a municipal administrative system which stands in marked contrast to our own.
Citation: Spilman, Harold Addison. Municipal government in Great Britain. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: History of Municipal Organization in England; Municipal Code; Practical Operation of the Code; Suggestibility; Hypnotic State; Theses